PENGEMBANGAN USAHA PETERNAKAN AYAM POTONG DI DESA PASINAN DALAM MENINGKATKAN KETAHANAN PANGAN DESA PASINAN KECAMATAN LEKOK MELALUI BUMDES - Ahmad Murtadlo; Muhammad Yusron Maulana El-Yunusi (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
The unstructured management of Tarawih imam schedules in mushalla of Pagerngumbuk Village leads to irregular rotation of imams and inadequate coordination among mushalla, affecting the effectiveness of Ramadan worship. This study aims to assist takmir (mosque management) in systematically organizing imam schedules to enhance the orderliness and solemnity of worship. The research adopts a qualitative case study approach using Participatory Action Research (PAR), involving takmir, imams, and worshippers as research subjects. Data were collected through in-depth interviews, participant observations, and documentation, and analyzed using Miles and Huberman's techniques, including data reduction, data display, and conclusion drawing. The findings reveal that implementing the PAR approach significantly improves the regularity and effectiveness of Tarawih prayers by actively involving the community in creating a more structured imam schedule. Moreover, the program provides opportunities for young aspiring imams to practice leadership in congregational prayers. This assistance not only enhances worship effectiveness but also contributes to strengthening religious leadership capacity at the community level.